PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) - Nugrahanti, Yeterina Widi; Wijaya, Nathalia (Jurnal Manajemen dan Keuangan, 2011)
The purpose of this study is to examine the effect of firmâs characteristic on corporate social responsibility disclosure in Manufacturing Indonesian companies. The corporate social responsibility disclosures include details of the environment, energy, employee health and safety,employee other, products, community involvement, and general. The firmâs characteristic is measured by company size, profitability,size of board of commissioner, company profile and leverage.The sample of this research was extracted with purposive sampling method. The sample of the study consist of 76 annual reports of manufacturing companies listed on the Indonesian Stock Exchange as of December 31, 2009. The technique for examining hypothesis is multiple regression analysis by using SPSS 16.00 programs. The results indicate that company size and size of board of commissioner have a significant positive influence on the corporate social responsibility disclosure. But profitability, company profile and leverage failed to show its significant effect.Keyword: Corporate social responsibility disclosure, Company size, Profitability, Size of board of commissioner, Leverage